Afro-Uruguayan literature post-colonial perspectives - Lewis, Marvin A. 1942- (Bucknell University Press, 2003)
"This study is about representation and resistance in Afro-Uruguayan culture: representation primarily through literary expression in black periodicals, and resistance to total domination by the majority Euroentric culture through popular expression associated with the African heritage. This book explores the manner in which Afro-Uruguayans defined, and continue to affirm, their "place" in a country in which societal and self perceptions were/are constantly shifting. This is a continuing process to which the written record holds the key. It has been common knowledge among literary historians that Afro-Uruguayans published a number of periodicals beginning as early as 1872. It is only now, however, with recent discoveries in the National Library in Montevideo that the extent of this production has become evident. It is primarily through these periodicals, the focus here, that much of the cultural legacy of Afro-Uruguayans can be reconstructed."--BOOK JACKET.